A Narrative Review of Function-Focused Measures for Children With Neurodevelopmental Disorders - Shanmugarajah, Kajaani; Rosenbaum, Peter; Zubairi, Mohammad; Di Rezze, Briano (Frontiers in Rehabilitation Sciences, 2021)
Clinical measures in health and rehabilitation settings are often used to examine child functioning to better support the diverse needs of children with neurodevelopmental disorders (NDD) and their families. The WHO’s International Classification of Functioning, Disability, and Health (ICF) framework reflects a focus of health beyond biomedical deficits using the concept of functioning to create opportunities for measurement development involving this construct. In the measures developed in the field of childhood NDD, it is unclear whether and how these tools measure and incorporate the ICF framework and its domains within health care contexts. Understanding how these measures utilize the ICF will enable researchers and clinicians to better operationalize function-focused concepts in studies and clinical practice. This narrative review aims to identify and describe function-focused measures that are based on the ICF for children with NDD, as described in the peer-reviewed literature. This review used a systematic search strategy with multiple health-focused databases (Medline, PsycInfo, EMBASE, EMCARE), and identified 14 clinical measures that provide direct support for children (aged 0-21) with NDD in paediatric health (and other) settings. Results described the measures that were primarily developed for three main diagnostic populations [cerebral palsy, autism spectrum disorder, and communication disorders]; had varying contextual use (clinical-only or multiple settings); and for which had conducted psychometric tests in the measure’s initial development studies, with the most common being content validity, interrater reliability, test-retest reliability. Participation (79%, n=11) & Activities (71%, n=10) were the most common ICF domains captured by the set of measurement tools. Overall (71%, n=10) of the identified measures utilized multiple ICF domains, indicating that the ‘dynamic nature’ of the interactions of the ICF domains was generally evident, and that this result differentiated from ‘linking rules,’ commonly used in research and clinical practice. The implications of these findings suggest that clinical measures can be an effective application of the ICF’s defined concepts of functioning for children with NDD.